International stock exchange listings : evidence from Singapore. - Low, Wee Khng. (2009)
The report provides some comprehensive reviews on the past studies on the motivation factors which would motivate firms to be listed on foreign stock exchanges. There has been a growing trend for firms to perceive the benefits derived form listing their stocks on foreign exchanges as outweighing the related costs. This report investigates the level of importance and relevance of various possible motivation factors in the Singapore context relative to global markets i.e. for Singapore firms to list on foreign stock exchanges and vice-versa for foreign firms to list on SES. The report also includes some examples of Singapore companies listed on foreign stock exchanges as well as foreign company listed on the Stock Exchange of Singapore.